Sex-related differences in the concentrations of apolipoprotein E in human blood plasma and plasma lipoproteins. - N R Phillips; R J Havel; J P Kane (Journal of Lipid Research, 1983)
Apolipoprotein E (apoE) and lipoprotein cholesterol and triglycerides were measured in blood serum of 272 persons randomly selected from a large industrial population in northern California. Serum apoE level increased linearly by 0.013 mg/dl with each 1 mg/dl increase in very low density lipoprotein (VLDL) triglycerides. This estimate was independent of sex and the use of sex hormones by women. Compositional studies of isolated apoVLDL in 156 hypertriglyceridemic men and 162 normotriglyceridemic persons of both sexes from the same population also indicated that the content of apoE was independent of VLDL level, sex, and hormone use. The estimate of the relationship between serum apoE and VLDL-triglycerides derived from these compositional studies was comparable to that derived by regression analysis. Regression analysis also indicated that only 10-20% of the apoE in the serum of the average person is in the VLDL fraction. Serum apoE levels were 1.4 mg/dl higher in women than in men with the same VLDL-triglyceride level and 1.8 mg/dl lower in women using contraceptive drugs than in nonusers of like age and VLDL-triglyceride level.